Optimizing the Performance of the State Civil Apparatus through Increasing Employee Discipline (Study at the Social Service of Sumedang Regency) - Bekti, Herijanto (HK-Publishing, 2022)
AbstractDiscipline of the State Civil Apparatus or commonly called ASN is an absolute thing that must be done if you want to improve performance. Work discipline is a problem that always occurs in every organization, including the Social Service of Sumedang Regency. One effort to improve the discipline of ASN is to provide employee training in collaboration with institutions or third parties regarding training that is mental and training that improves work skills competence. Therefore, the purpose of this study is to improve the level of employee discipline in order to enhance the efficiency of the state's civil machinery. In this investigation, a qualitative strategy is combined with a descriptive research approach. According to the findings of the study, discipline is of utmost significance in terms of enhancing the performance of the State Civil Apparatus, indicating the necessity of occupational training. In this study, the authors propose 6 scopes of work training that must be carried out by ASN to improve their work discipline, namely employee motivation development training, leadership training, effective communication technique training, self-introduction training and acknowledgment management training.Keywords: Performance, Discipline, Training, State Civil Apparatus.Â AbstrakDisiplin Aparatur Sipil Negara atau biasa disebut ASN merupakan hal mutlak yang harus dilakukan jika ingin meningkatkan kinerja. Disiplin kerja merupakan masalah yang selalu terjadi di setiap organisasi, termasuk Dinas Sosial Kabupaten Sumedang. Salah satu upaya untuk meningkatkan kedisiplinan ASN adalah dengan memberikan pelatihan pegawai bekerja sama dengan lembaga atau pihak ketiga mengenai pelatihan yang bersifat mental dan pelatihan yang meningkatkan kompetensi keterampilan kerja. Oleh karena itu, tujuan dari penelitian ini adalah untuk meningkatkan tingkat kedisiplinan pegawai dalam rangka peningkatan efisiensi mesin sipil negara. Dalam penelitian ini, strategi kualitatif dipadukan dengan pendekatan penelitian deskriptif. Menurut temuan penelitian, disiplin sangat penting dalam hal peningkatan kinerja Aparatur Sipil Negara, menunjukkan perlunya pelatihan kerja. Dalam penelitian ini, penulis mengusulkan 6 lingkup pelatihan kerja yang harus dilakukan oleh ASN untuk meningkatkan disiplin kerja, yaitu pelatihan pengembangan motivasi karyawan, pelatihan kepemimpinan, pelatihan teknik komunikasi efektif, pelatihan pengenalan diri dan pelatihan manajemen pengakuan.Kata Kunci: Kinerja, Disiplin, Diklat, Aparatur Sipil Negara.